(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: Pseudoexfoliation syndrome is a common eye disorder that can affect different parts of the eye causing significant morbidity. Objective: To compare corneal endothelial changes between patients with pseudoexfoliation syndrome and normal age matched patients. Methods: Specular microscopy was used to measure central corneal thickness, average size of endothelial cells and coefficient of variation in cell area, endothelial cell density, as well as hexagonality of 238 eyes from 238 patients (120 eyes from patients with pseudo exfoliation syndrome and 118 eyes from normal age-matched patients). Results: Patients with pseudoexfoliation syndrome had lower central corneal thickness (p value 0.049) compared to the control (491.6±28.86 vs 502.5±35.77 µm), lower endothelial cell density (p value 0.02) compared to control (2458.9±430.8 vs 2585.3±378.8 cell/mm2), lower hexagonality (P value 0.006) compared to control (48.25±18.76 vs 55.06±12,44), also a significantly higher coefficient of variation (p value 0.046) compared to control (36.15±7.381 vs 33.4±6.22). Conclusion: Pseudoexfoliation syndrome is associated with a significant change in the corneal endothelium, including reduction of endothelial cell density, increased variation of cells shape (pleomorphism) and increased variation of cells area (polymegathism). There was a significant change of central corneal thickness. Keywords: Corneal endothelium, specular microscopy, pseudoexfoliation syndrome, central corneal thickness Citation: Rasheed AM, Kadum DJ. Corneal changes in a sample of pseudoexfoliation Iraqi patients. Iraqi JMS. 2018; 16(3): 232-238. doi: 10.22578/IJMS.16.3.2